Revision of the type series of Empis (Planempis) mandarina Frey, the type species of Planempis (Diptera: Empididae) - Saigusa, Toyohei (Zootaxa, 2012)
The type series of Empis (Planempis) mandarina Frey, 1953, the type species of Planempis Frey, from Fukien (Fujian), Chinaand Kambaiti, Myanmar is revised and found to include four species. The lectotype is designated for a Fukien male specimen.Two other species, E. (Planempis) lindebergi sp. nov. and E. (Planempis) janssoni sp. nov. are described based on a male syn-type, and a male and three female syntypes from Kambaiti, respectively. A species represented by females from Fukien is not conspecific with any of these species and remains unnamed.